2017
DOI: 10.3390/app7090882
|View full text |Cite
|
Sign up to set email alerts
|

Design of 1-Bit Digital Reconfigurable Reflective Metasurface for Beam-Scanning

Abstract: A 1-bit digital reconfigurable reflective metasurface (RRM) with 20 × 20 cells is presented, fabricated and measured for beam-scanning performance in this paper. The cell is designed with a single layer structure and one varactor diode, controlled electronically. The cell's phase compensation is over 180 • between 3 GHz and 4 GHz and the two states with 180 • phase difference are selected as coding "0" and coding "1". By the fuzzy quantification theory, all the elements on the RRM are set to be coding "0" or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…At oblique incidence, an effective RCS reduction characteristic can also be achieved. Compared with previous works [21][22][23][24][33][34][35][36][37][38][39][40][41][42], our design of the matrix-type random coding MSs has better broadband RCS reduction and wide-angle incidence tolerance. The designed MS is expected to have potential applications in the field of stealth.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…At oblique incidence, an effective RCS reduction characteristic can also be achieved. Compared with previous works [21][22][23][24][33][34][35][36][37][38][39][40][41][42], our design of the matrix-type random coding MSs has better broadband RCS reduction and wide-angle incidence tolerance. The designed MS is expected to have potential applications in the field of stealth.…”
Section: Discussionmentioning
confidence: 88%
“…Then, six kinds of MSs based on split-ring resonator (SRR) structure were designed to explore the RCS reduction characteristic. Compared with previous works [21][22][23][24][33][34][35][36][37][38][39][40][41][42], our design has some advantages: Firstly, new random coding method with novel mechanism; Secondly, the structure of basic unit is simple, which can achieve the characteristics of 180 • cross-polarization phase differences by simply rotating the metal cut-wire structure; Thirdly, our design presents the RCS reduction at lower frequency with high relative bandwidth compared with the works published before. Such a simple and effective design may provide some potential applications in the field of stealth.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Since then, several works and progress have been made in this area [5][6][7]. Different designs of 1-bit unit cell and metasurface have been proposed in [8][9][10][11][12][13]. Yang and colleagues proposed a simple rectangular element but working effectively in metasurface.…”
Section: Introductionmentioning
confidence: 99%
“…In these papers, the authors theoretically and experimentally demonstrated that the 1-bit metasurface is capable of digital beam focusing, multibeam focusing, scattering, and broadside beam synthesis. A 1-bit digital reconfigurable reflective metasurface with 20 × 20 cells is presented for beam-scanning in [13]. In that work, the authors used a varactor diode instead of a PIN diode for achieving wider bandwidth.…”
Section: Introductionmentioning
confidence: 99%